2006
DOI: 10.1111/j.1440-169x.2006.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gbx2 and Otx2 in the formation of cochlear ganglion and endolymphatic duct

Abstract: The boundary of gene expression of transcription factors often plays a role in making a signaling center in development. In the otic vesicle, Gbx2 is expressed in the dorso-medial region including the endolymphatic duct, and Otx2 in the ventral region. Fgf10 is expressed between their expression boundaries, and the cochleovestibular ganglion develops close to the medial side of the Fgf10 expressing domain. Similar expression patterns are observed in the central nervous system, where Otx2 and Gbx2 expression ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Lmx1a , and Otx1. Otx2 regulates Fgf10 (an upstream activator of N-Myc ) expression in the otic placode of chicken (Bok et al, 2005; Miyazaki et al, 2006) and a link between increased levels of Otx2 and N-Myc was shown in meduloblastomas, suggesting that Otx2 and N-Myc may form a feedback loop (Adamson et al, 2010). Otx2 is found in the cochlea while Otx1 is present in the vestibular epithelia (Morsli et al, 1999) and while there appears to be a possible connection between Otx2 and N-Myc , the interaction between Otx1 and N-Myc remains unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…Lmx1a , and Otx1. Otx2 regulates Fgf10 (an upstream activator of N-Myc ) expression in the otic placode of chicken (Bok et al, 2005; Miyazaki et al, 2006) and a link between increased levels of Otx2 and N-Myc was shown in meduloblastomas, suggesting that Otx2 and N-Myc may form a feedback loop (Adamson et al, 2010). Otx2 is found in the cochlea while Otx1 is present in the vestibular epithelia (Morsli et al, 1999) and while there appears to be a possible connection between Otx2 and N-Myc , the interaction between Otx1 and N-Myc remains unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Otx2 is an important early otic patterning gene and is required for establishment of the neurogenic domain by repressing Fgf10 expression (Miyazaki et al, 2006). As both Otx2 and Fgf10 expression are absent from Chd7 null otocysts, CHD7 may regulate Fgf10 in an OTX2-dependent manner.…”
Section: Research Articlementioning
confidence: 99%
“…We tested whether reduced CHD7 impacts expression of genes implicated in E9.5-E10.5 otocyst patterning. Otx2, which regulates cochlear patterning and ganglion development (Miyazaki et al, 2006;Morsli et al, 1999), was retained in E10.5 Chd7 Gt/+ and conditional heterozygotes, but was absent from conditional null and Chd7…”
Section: Expression Of Otx2 Fgf10 and Ngn1 Within The Otocyst Is Chdmentioning
confidence: 99%
“…In addition, ventral otic derivatives-the cochlea and spiral ganglion-are malformed in both mutants, even though Gbx2 is not expressed in ventral otic domains. This may be due, at least in part, to mutually repressive interactions between Gbx2 and Otx2 (Lin et al, 2005;Choo et al, 2006;Miyazaki et al, 2006). Gbx2 is required for Wnt2b and medial Dlx5/6 expression, which is also lost in kr/Mafb mutants (Lin et al, 2005;Choo et al, 2006).…”
Section: Intrinsic Factors For Interpretation Of Dv/ml Patterningmentioning
confidence: 99%